Improving the Understanding of Private Islamic Senior High School Students at Diniyah Limo Jurai Regarding the Jurisprudence of Worship through Project-Based Learning Models - Apriani, Wilda; Wilastuningsih; Istianah, Wilayatul; Wijiarti; Asmini, Wiji (Journal of Media and Learning Technology, 2025)
Students’ understanding of the subject of Fiqh Ibadah is an important aspect in Islamic education, especially at the Madrasah Aliyah level. However, in practice, many students have difficulty in understanding the concepts of Fiqh in depth due to the learning approach which is still conventional and does not involve direct experience. This study aims to analyze the effectiveness of the application of the project-based learning model (PjBL) in improving the understanding of class X students of MAS Diniyah Limo Jurai towards Fiqh Ibadah. This study uses the classroom action research (CAR) method which is carried out in two cycles. Each cycle consists of the planning stage, action implementation, observation, and reflection. Data were collected through comprehension tests, observations, interviews, and documentation, which were then analyzed descriptively qualitatively and quantitatively. The results of the study showed that the application of the PjBL model had a positive impact on students’ understanding. There was a significant increase in students’ understanding test results from the pre-cycle to the first cycle, and a further increase in the second cycle. In addition, this approach also increases students’ active involvement in learning, encourages creativity, and fosters an attitude of cooperation and independence in understanding the material of Fiqh Ibadah. The conclusion of this study is that the project-based learning model can be an effective strategy in improving students' understanding of Islamic Jurisprudence. Therefore, it is recommended that educators apply this model more in learning in order to improve the quality of students' understanding of religious material.